Filling in the Gaps: Remembering the 1965 Killings in Indonesia - Leong, Kar-Yen (Archīum Ateneo, 2024)
After more than fifty years, Indonesia remains muted in its acknowledgement of the killings and disappearances of nearly one million suspected leftists in the anti-Communist pogroms of 1965. While the downfall of Indonesian strongman Suharto had opened up a larger space for democracy, the Indonesian state remains reticent in facing accusations of mass human rights violations that have taken place during his rule. Although many former dissidents and political detainees have come forward with their stories in an effort to “straighten history,” they continue to face harassment from right wing groups as well as the state’s intelligence apparatus. Nevertheless, with the advent of the Internet, human rights activists as well as historical “revisionists” have begun to use the cyber sphere as way to fill in the “gaps” in terms of Indonesia’s narrative concerning the killings of 1965. This paper investigates the dynamics behind the use of this medium in transmitting this dark episode to a younger generation of Indonesians. It looks specifically at Ingat 1965, a website that utilizes “private memory” as a way to “resist” as well as reinvent the narrative, which has so long been dominated by the state. This paper also includes an investigation into how Indonesia is beginning to deal with its past.